Publication Trends in Food-Borne Disease Research (1991–2015): A Web of Science Core Collection Based Analysis. Issue 1 (2nd January 2017) - Kolle, Shankar Reddy; Shankarappa, T. H.
ABSTRACT: This article analyzes publication trends in food-borne disease research for the period 1991–2015, using data collected from the Web of Science Core Collection. A total of 11, 725 research articles were used in the analysis. Results showed that the number of publications rose exponentially during the period of study. The average number of authors per article also increased. "Food Science & Technology" was the leading subject category under which the majority of articles placed. The Journal of Food Protection was the most productive journal with 794 articles. "Kang, DH" was the most productive author and the United States was the most productive country, followed by China.